PENGARUH PROMOTION MIX TERHADAP KEPUTUSAN PEMBELIAN CAT TEMBOK MEREK ENVI DENGAN KUALITAS PRODUK SEBAGAI VARIABEL MODERASI - Setyaningsih Sri Utami, Wahyu Mudomo, Ernawati & (Universitas Slamet Riyadi, 2016)
The purpose of this study was to determine what factors are affecting the sales increase in the production of wall paint brand Envi PT Indaco and what factors most dominant influence. The hypothesis of this study is suspected factors that affect the sales increase in the production of wall paint brand Envi PT Indaco is a factor of promotion mix. Sources of data in this research is secondary data obtained from PT Indaco and primary data obtained from questionnaires to 100 respondents. Data were analyzed using multiple linear regression and test of absolute difference. The results showed that the promotion mix negatively affect purchasing decisions. The product quality has positive influence on purchase decisions. The quality of the product does not moderate promotion mix on purchasing decisions.Keywords: promotion mix , product quality , purchasing decisions